Endurance testing of the additively manufactured STAR resistojet. (15th October 2019) - Robinson, M.; Grubišić, A.; Rempelos, G.; Romei, F.; Ogunlesi, C.; Ahmed, S.
Abstract: This paper reports the outcome of endurance tests performed on a proof-of-concept design of a high-temperature resistojet thruster. A high-performance resistojet could enable a fully all-electric spacecraft architecture providing all propulsion system functions. The thruster utilises a novel additive-manufactured heat exchanger, consisting of concentric thin-walled cylinders, which act as both a resistive heating element and regenerative heat exchanger. Two complete thruster assemblies were tested, with heat exchangers manufactured from 316L stainless steel using selective laser melting. The two test units were used to investigate the operational endurance and determine life-limiting failure modes of the design. The tests consisted of repeated operational cycling to known temperature limits while under vacuum. Degradation and failure was inferred from electrical characteristics of the thrusters, and X-ray computed tomography imaging was used for non-destructive inspection both pre- and post-testing. The analysis showed that the failure modes are due to thermally-induced stresses resulting from mechanical constraints and temperature gradients. The failures occurred after approximately 40 cycles in the first thruster operating with a current of 25 A, and, in the second thruster, after a total of 300 cycles at 15 A and 217 cycles at 20 A, resulting in two distinctly different failure locations. Graphical abstract: Unlabelled Image Highlights: A novel additive-manufactured resistojet thruster is tested to investigate cycle life under high-temperature conditions. X-ray tomography and in-situ electrical measurements are combined to diagnose failures of the additive-manufactured heater. Thermomechanical stresses are found to cause premature failure in additive-manufactured heaters from 316L stainless steel.